Factors influencing risky sexual behaviour among rural South African high school girls - Mulaudzi , Shumani; Hoque, Muhammad (Orapuh Journal, 2025)
IntroductionA person is said to engage in risky sexual behaviour when participating in activities that increase their susceptibility to sexual and reproductive health problems. Risky sexual behaviour among adolescents is a major public health issue in rural South Africa, where access to sexual health education and services is limited. These behaviours heighten the risk of unintended pregnancies and sexually transmitted infections (STIs), including HIV, and negatively affect the long-term health and socioeconomic status of young girls. Identifying contributing factors is crucial for developing effective interventions.PurposeThis study aims to identify and quantify factors influencing risky sexual behaviour among high school girls in Limpopo Province, South Africa, to inform targeted interventions.MethodsA cross-sectional survey of 306 high school girls (grades 10–12) from five rural schools was conducted. Data were collected using structured questionnaires. Logistic regression was applied to analyse significant factors associated with risky behaviours.ResultsTwo-thirds of the participants reported engaging in risky sexual behaviours, including having multiple sexual partners. Among grade 10 learners, age, sexual experimentation, multiple sexual partners, and engaging in sex for gifts were statistically significant predictors of risky sexual behaviour (p < 0.05). Overall, experience of gender-based violence was found to be a significant predictor of risky sexual behaviour (p < 0.05).ConclusionThe study underscores the need for comprehensive sexual education in rural South African schools. Interventions should include gender-sensitive and culturally relevant sexual education, tailored to the socioeconomic realities of rural South Africa, to reduce the risks associated with adolescent sexual practices.